Caruso 1873 [compact disc] - Alagna, Roberto; Kurzak, Aleksandra, 1977- (Sony Classical, 2019)
Roberto Alagna honors his legendary predecessor with a selection of repertoire drawn from Caruso's own recording career, which stretched from 1902 to 1920. Alagna's aim was to celebrate Caruso while retaining his own vocal identity.